The Influence of Workload on Performance with the Mediation of Village Apparatus Motivation in Grabag District - Salsabilaa; Hardin; Fitri Rahmawati (www.amertainstitute.com, 2025)
This research investigates a notable trend among village officials who frequently delay their tasks, extend their working hours, and undertake responsibilities beyond their official roles due to overwhelming workloads. Furthermore, a lack of motivation is apparent, as evidenced by delayed salary disbursements and insufficient recognition from superiors. These factors are believed to adversely affect employee performance. The research seeks to: (1) examine how workload affects employee performance., (2) Evaluate the impact of workload on work motivation. (3) Analyze the relationship between work motivation and employee performance. (4) Explore the intermediary function of work motivation in the association between workload and employee performance. among village officials in the Grabag District of Purworejo Regency. A quantitative research approach employing a survey technique. was employed, with data gathered from questionnaires distributed to 376 village officials. Proportional random sampling was the technique used, the sample size was determined using Slovin’s formula, yielding a total of 194 participants. The data were analyzed using Partial Least Squares (PLS) through the SmartPLS 4.0 software. This analysis encompassed evaluation of the measurement model (covering validity and reliability tests), structural model (including R-square and f-square values), and hypothesis testing via the bootstrapping method. The analysis revealed several key findings: (1) workload has a significant adverse influence on employee performance; (2) workload also negatively affects work motivation in a meaningful way; (3) work motivation exerts a strong positive influence on employee performance; and (4) work motivation serves as a crucial intermediary variable, bridging the link between workload and performance outcomes. These insights imply that increased workload tends to diminish work motivation, subsequently leading to a decline in performance. Therefore, it is crucial for village leaders to ensure equitable workload distribution and provide sufficient motivational support to enhance the performance of village officials.